1983
DOI: 10.1002/jhet.5570200137
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of geometric isomers of norbornene end‐capped imides

Abstract: Three geometric isomers from the thermal isomerization of methylene‐4,4′‐bis(endo‐N‐phenylbicyclo‐[2.2.1]hept‐2‐ene‐5,6‐dicarboximide) (I) were chromatographically separated and isolated. Nmr spectroscopy was used to assign endo‐endo (I), endo‐exo (II), and exo‐exo (III) configurations to each compound. The three isomers, which serve as model compounds for norbornene end‐capped polyimides, were then characterized by several chromatographic, spectroscopic, and thermal techniques. Upon heating, each isomer was f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1983
1983
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…The C-H stretch region has been shown to be sensitive to the conformation of the norbornene end group. 17 Nadic anhydride exists as endo and exo isomers and, as can be seen from Fig. 8, the spectra of the two conformations are markedly different.…”
Section: Discussionmentioning
confidence: 89%
“…The C-H stretch region has been shown to be sensitive to the conformation of the norbornene end group. 17 Nadic anhydride exists as endo and exo isomers and, as can be seen from Fig. 8, the spectra of the two conformations are markedly different.…”
Section: Discussionmentioning
confidence: 89%
“…The influence of oxygen in the cure behavior of endo-endo, endo-exo, and exo-exo bisnadimide isomers was investigated by Young and Chang. 19 This work strongly showed that oxygen influenced crosslinking of the exo isomer to a much greater extent that the endo isomer. The weight loss of the exo isomer cured in air was significantly less than the endo isomer cured in the same manner.…”
Section: (B) Kinetics Of Thermal Curementioning
confidence: 95%
“…The reactions which occur when a nadic end-cap compound or oligomer undergoes a thermally induced cross-linking reaction have been investigated and the cross-linked structures initially proposed [1][2][3] (figure 1), have been under scrutiny. There have been several mechanism studies on model compounds, and these studies have contributed to defining the cross-linked structure [3][4][5][6][7][8][9][10]. However, solid state 13 C NMR studies by Meador et al [11] on the cure of PMR-15, a nadic end-capped polymide [12], using 13 C labeled 4,4 1 methylenedianiline provided new evidence and insight for the structure involved in the cross-linking reaction as a result of cure at 315 2 C for 1.5 h. These investigators propose a radical-induced homopolymerization mechanism to define the major product, shown in figure 1(d).…”
Section: Introductionmentioning
confidence: 99%